Answer:
x = 12.48
Explanation:
Simplifying
12(x + -13) = 13(12 + -1x)
Reorder the terms:
12(-13 + x) = 13(12 + -1x)
(-13 * 12 + x * 12) = 13(12 + -1x)
(-156 + 12x) = 13(12 + -1x)
-156 + 12x = (12 * 13 + -1x * 13)
-156 + 12x = (156 + -13x)
Solving
-156 + 12x = 156 + -13x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '13x' to each side of the equation.
-156 + 12x + 13x = 156 + -13x + 13x
Combine like terms: 12x + 13x = 25x
-156 + 25x = 156 + -13x + 13x
Combine like terms: -13x + 13x = 0
-156 + 25x = 156 + 0
-156 + 25x = 156
Add '156' to each side of the equation.
-156 + 156 + 25x = 156 + 156
Combine like terms: -156 + 156 = 0
0 + 25x = 156 + 156
25x = 156 + 156
Combine like terms: 156 + 156 = 312
25x = 312
Divide each side by '25'.
x = 12.48
Simplifying
x = 12.48